Jawara on the Stage of Political Power in Banten - Davi Dwi Julio; Nadia Khumairatun; Sultan Nadhifa; Rafael Kamajaya; Muhammad Daffa Pratama; Muhammad Wafikurrizky Nugraha; Silpius Kegiye (Sean Institute, 2026)
This researcher investigates the transformation and strategic role of jawara as traditional cultural figures who have transitioned into influential political actors within the regional power structure of Banten, Indonesia. Drawing on Michel Foucault’s theory of power relations, this research examines how jawara negotiate, construct, and sustain power through complex interactions between cultural authority, kinship networks, state institutions, and political dynamics. Employing a qualitative single instrumental case study approach, this study analyzes documentary data, academic literature, historical records, and media sources to uncover patterns of influence embedded in both formal and informal political spheres. Findings reveal that the power of jawara in Banten is institutionalized through several mechanisms: genealogical legitimacy rooted in aristocratic titles, the penetration of state elites into cultural organizations, the use of kinship-based networks for electoral mobilization, and the provision of state resources to reinforce dependency. These mechanisms demonstrate that the jawara’s authority transcends physical or martial strength, evolving into a sophisticated form of socio-political power embedded in historical narratives, cultural symbols, and governance practices. Consequently, the relationship between jawara and the state reflects a hybrid political order where traditional authority and modern bureaucracy intersect, reinforcing reciprocal legitimacy and reproducing local elite domination.